Effects of high‐speed shear homogenization on the emulsifying and structural properties of myofibrillar protein under low‐fat conditions. (16th August 2019) - Zhou, Lei; Feng, Xiao; Yang, Yuling; Chen, Yinji; Tang, Xiaozhi; Wei, Sumeng; Li, Shanshan
Abstract: BACKGROUND: Emulsification is important for food quality and processing functionality. Most emulsification occurs under high‐fat conditions that eventually cause health concerns. Protein emulsifiers also have drawbacks such as lower dispersity. This study considered the effects of different high‐speed shear homogenization (HSH) speeds on the emulsifying and structural properties of myofibrillar proteins (MPs) under low‐fat conditions. RESULTS: High‐speed shear homogenization significantly increased the emulsifying activity and emulsifying stability of MPs at lower speeds (8000 to 14 500 rpm). The primary structure of MP was not altered significantly by HSH, whereas its secondary, tertiary, and quaternary structures were changed. Particle size decreased first and then increased significantly, and reached a minimum when the HSH speed was 14 500 rpm. The absolute zeta potential values increased significantly and the dendritic fibrous structure of sample was destroyed when the speed exceeded 14 500 rpm. High‐speed shear homogenization (14 500 rpm) decreased the particle size and unfolded the protein, which improved the emulsifying properties of MPs. Excessive HSH speeds (20 500 rpm or higher) caused an aggregation of MP molecules, which was not conducive to improving their emulsifying properties. CONCLUSION: Optimal HSH speed was achieved at 14 500 rpm to modify MPs' emulsifying and structural properties under low‐fatconditions. © 2019 Society of Chemical Industry